Subliminal voices: barriers to healthcare and proposed interventions by international students and their families at a large research university in the Midwest - Sen, Soumitro (Frontiers in Communication, 2023)
Despite the vast numbers of international students in the U.S. as well as their contribution to the economy, their voices are rarely heard within the discursive spaces of the American academe. This study takes a step towards filling that gap and examines, in particular, barriers that married, international graduate students at a large Midwestern university faced while accessing healthcare facilities for their families. Using a culture-centered approach to health communication, this study allowed 22 international students and spouses to communicate vivid narratives of the problems they encountered while negotiating the American healthcare system. This study also presents ideas of interventions that international students proposed to redress the problems.